Happiness in dermatology: a holistic evaluation of the mental burden of skin diseases. (19th January 2020) - Schuster, B.; Ziehfreund, S.; Albrecht, H.; Spinner, C.D.; Biedermann, T.; Peifer, C.; Zink, A.
Abstract: Background: According to the World Health Organization, mental health is a state of well‐being and not merely the absence of disease. However, studies exploring subjective well‐being in patients with skin diseases are very rare. Objectives: To assess subjective well‐being, i.e. 'happiness', in patients with different skin diseases and to compare them to other patient groups and healthy controls. Methods: A cross‐sectional study was conducted from 12/2017 to 04/2019. Patients receiving in‐ or outpatient care for psoriasis, atopic eczema, nummular eczema, mastocytosis, skin cancer (malignant melanoma and keratinocyte carcinoma), human immunodeficiency virus (HIV) or chronic inflammatory bowel diseases (Crohn's disease and ulcerative colitis) were recruited at two hospitals in Bavaria, Germany. Healthy individuals living in or near Munich served as a control group. All participants filled in a questionnaire assessing happiness, measured as positive affect (PA), negative affect and satisfaction with life (SWL; together representing subjective well‐being) and a heuristic evaluation of one's own happiness. Results: Data from 229 dermatologic patients (53.3 ± 18.5 years, 48% women), 49 patients with inflammatory bowel diseases (48.9 ± 18.7 years, 43% women), 49 patients with HIV (46 ± 10.1 years, 10% women) and 106 healthy controls (38.4 ± 13.4 years, 49% women) were analysed. Compared to the controls, dermatologic patients reported lower heuristic happiness ( P = 0.023) and PA ( P = 0.001) but higher SWL ( P = 0.043). Patients with psoriasis and atopic eczema reported the lowest happiness, as they reported significantly lower PA ( P = 0.032 and P < 0.001) and heuristic happiness ( P = 0.002 and P = 0.015) than the control group. Patients with skin cancer reported higher SWL than the control group ( P = 0.003). Dermatologic patients reported lower happiness than patients with HIV but reported greater happiness than patients with IBD. Conclusions: Dermatologic patients experience lower levels of happiness, especially PA, compared to healthy controls. As PA is linked to desirable health outcomes, targeting PA could be a promising holistic approach for the treatment of skin diseases.